Bisexuality in the ancient world - Cantarella, Eva (Yale University Press, 1992)
"Bisexuality was intrinsic to the cultures of the ancient world. In both Greece and Rome, same gender sexual relationships were acknowledged, and those between men were not only tolerated but widely celebrated in literature and art. Nor for Greeks and Romans was homosexuality an exclusive choice, but alternative to and sometimes concurrent with the love of the opposite sex." "Whilst exploring aspects of the female condition in Classical antiquity, Eva Cantarella came to understand that the sheer ubiquity of male homosexuality had a fundamental impact on relationships between men and women. Drawing on the full range of surviving sources - legal texts, inscriptions, medical documents, poetry and philosophical literature - she now reconstructs the homosexual cultures of Greece and Rome and provides a full, readable and thought-provoking history of bisexuality in the Classical age." "Cantarella explores the psychological, social and cultural mechanisms that determined sexual choice and consider: the extent to which that choice was free, directed or coerced in each civilization. In Greece the relationship between adults and youngs[sic] boys was deemed the noblest of associations, a means of education and spiritual exhaltation[sic]. Cantarella reveals that such relationships, though highly regulated and never left to individual spontaneity, were more than pedagogic and platonic: they were fully carnal. In Imperial Rome, however, the sexual ethic mirrored the political and males were cruelly domineering in love as in war. The critical sexual distinction was that between active and passive, the victims commonly being slaves or defeated enemies, rather than young Roman freemen."